Dexamethasone Administration During Late Gestation Has No Major Impact on Lipid Metabolism, but Reduces Newborn Survival Rate in Wistar Rats - Motta, Katia; Gomes, Patricia R. L.; Sulis, Paola M.; Bordin, Silvana; Rafacho, Alex (Frontiers in Physiology, 2018)
A rise in plasma triacylglycerol levels is a common physiological occurrence during late gestation and excess of glucocorticoids (GCs) have been shown to impair lipid metabolism. Based on those observations, we investigated whether the administration of dexamethasone during the late gestational period could exacerbate this pregnancy associated hypertriacylglycerolemia in rats. For this, female Wistar rats were treated with dexamethasone (0.2 mg/Kg of body mass in the drinking water on days 14 to 19 of pregnancy) (DP group) or equivalent days in the virgin rats (DV group). Untreated pregnant rats (CP group) and age-matched virgin rats (CV group) were used as controls. Functional, biochemical and molecular analysis were carried out after treatment with GC and in the control groups. Euthanasia was performed on day 20 of pregnancy. The metabolic parameters of the mothers (dams) at the time of weaning and six months later, as well as newborn survival, were evaluated. We observed that neither dexamethasone nor pregnancy affected blood glucose or glucose tolerance. Hypertriacylglycerolemia associated with lipid intolerance or reduced hepatic triacylglycerol clearance was observed during the late gestational period. GC treatment caused a further increase in basal plasma triacylglycerol levels, but did not have a significant effect on lipid tolerance and hepatic triacylglycerol clearance in pregnant rats. GC, but not pregnancy caused few significant changes in mRNA expression of proteins involved in lipid metabolism. Dexamethasone during pregnancy had no impact on lipid metabolism later in the dams’ life; however, it led to intra-uterine growth restriction and reduced pup survival rate. In conclusion, GC exposure during the late gestational period in rats has no major impact on maternal lipid homeostasis soon after parturition at weaning, or later in the dams’ life, but GC exposure is deleterious to the newborn when high doses are administered at late gestation. These data highlight the importance of performing an individualized and rigorous control of a GC treatment during late pregnancy considering its harmful impact on the fetuses’ health.